A Three-Input Central Capacitor Converter for a High-Voltage PV System - Meng, Xiangjian; Liu, Jiaxin; Wang, Gongke; Fang, Jingyang (Frontiers in Energy Research, 2022)
High voltage PV techniques have their own advantages in PV plants for reducing construction cost and improving operational efficiency. However, the high input PV voltage increases the mismatch losses of PV arrays, which is also a key factor that influences the energy yield of PV plants. This paper proposes a three-input central capacitor (TICC) dc/dc converter for high voltage PV system, where four low-rating cascaded buck-boost converters connect to the series-connected three low-voltage PV arrays and two capacitors and realize the maximum power point tracking (MPPT) independently. Meanwhile, there is a neutral point in the proposed converter, enabling it to be connected with the rear-end three-level inverter directly. It can also help balance the three-level dc-link voltage by properly regulating the transferred energy among three input sources. Compared with other transformer-less dc-dc converters, the proposed converter is able to reduce the semiconductor voltage/current stress and therefore achieve the high efficiency. Simulation and experimental results verified the performance of the proposed TICC converter.